An Eco-Friendly Solid-State Electrode Modified With ZnO Nanoparticles Decorated With MWCNT as an Electrochemical Sensor for the Determination of Avanafil in Pure Form, Dosage Form and Human Plasma. Issue 8 (24th August 2021) - Ali, Mohamed B.; Abdel-Raoof, Ahmed M.; Hendawy, Hassan A. M.; Talaat, Wael; Omran, Gamal A.; Morshedy, Samir
Abstract : A sensitive voltammetric technique for the determination of avanafil (AVA) has been investigated at a carbon paste electrode modified with Zinc oxide nanoparticles and multi-walled carbon nanotubes (ZnO-NPs/MWCNT/CP). The study investigated the electrochemical behavior of AVA, and the morphology of the modified electrode was evaluated by transmission electron microscopy, scanning electron microscopy, and X-ray diffraction patterns. The influence of different electrodes and the content of ZnO-NPs on the voltammetric behavior of AVA were evaluated. Square wave voltammetry was studied and a linear correlation resulted within the range of (1.3–16 μ g ml −1 ) with correlation coefficient 0.999, LOD 0.342 μ g ml −1 and LOQ 1.141 μ g ml −1 . The proposed procedure was applied successfully for the determination of AVA with good recovery in commercial dosage form and human plasma. The technique was validated and found to be accurate and reproducible according to the ICH guidelines.